2010
DOI: 10.2320/matertrans.m2010199
|View full text |Cite
|
Sign up to set email alerts
|

A New Austenitic FeMnAlCrC Alloy with High-Strength, High-Ductility, and Moderate Corrosion Resistance

Abstract: In this study, a new austenitic Fe-28%Mn-9%Al-6%Cr-1.8%C (in mass%) alloy is developed. Because the alloy contains a high density of fine (Fe,Mn) 3 AlC carbides within the austenite matrix, the alloy in the as-quenched condition exhibits an excellent combination of strength and ductility comparable to that of the aged FeMnAlC alloys. In addition, owing to the formation of a layer of Cr and Al oxides in the passive film formed on the alloys, the corrosion potential E corr (À538 mV) and the pitting potential E p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For some special purposes, e.g. to improve the oxidation and corrosion resistance, Cr is a usual element to be used in TWIP steels along with Al [13][14][15][16][17] .…”
Section: Alloying and Microstructures Of Twip Steelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For some special purposes, e.g. to improve the oxidation and corrosion resistance, Cr is a usual element to be used in TWIP steels along with Al [13][14][15][16][17] .…”
Section: Alloying and Microstructures Of Twip Steelsmentioning
confidence: 99%
“…In a recent study, Tsay et al [14] reported a new high manganese austenitic Fe-28Mn-9Al-6Cr-1.8C alloy with high-strength, high-ductility and moderate corrosion resistance. This alloy contains a high density of fine (Fe, Mn) 3 AlC carbides formed coherently within the austenite matrix during quenching.…”
Section: Anti-corrosion Behavior Of Twip Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsay et al studied the corrosion behavior of Fe−28Mn−9Al−6Cr−1.8C alloy in 3.5 wt.% NaCl [102]. Due to Cr and Al oxide formation, the E corr and E pit were −538 mV and −25 mV, respectively, significantly higher than −920 mV (∼−789 mV) and −500 mV (∼−240 mV) for E corr and E pit , respectively, of Fe−28Mn−9Al−6Cr−1.8C alloy.…”
Section: Effect Of Al and Cr Alloying On High-mn Twip Steel Corrosionmentioning
confidence: 99%
“…Fe−Mn−Al−C steel was first developed in late 1950s for the use of cryogenic or highly corrosive environments by replacing the high Fe−Ni−Cr SS cryogenic [219], and recently reappraised as a promising candidate for austenitic SS by adding some content of Cr [102].…”
Section: Corrosion Of High-mn Twip Steels In Harsh Environmentsmentioning
confidence: 99%